Morphological Diversity and Crop Mimicry Strategies of Weedy Rice Under the Transplanting Cultivation System - Yi-Ting Hsu; Yuan-Chun Wang; Pei-Rong Du; Charng-Pei Li; Dong-Hong Wu (Agronomy)
The continued emergence of weedy rice (Oryza sativa L.) in Taiwan poses serious challenges to seed purity and commercial rice cultivation, particularly under transplanting systems. These off-type individuals, often marked by a red pericarp, reduce varietal integrity and complicate seed propagation. This study evaluated the morphological variation among 117 Taiwan weedy rice (TWR) accessions and 55 control cultivars, which include 24 temperate japonica cultivars (TEJ), 24 indica cultivars, and seven U.S. weedy rice (UWR) types. Principal component analysis (PCA) showed that TWR shares vegetative traits with modern cultivars but exhibits grain morphology resembling indica landraces—indicating weak artificial selection pressure on grain traits during nursery propagation. TWR was also found to possess a suite of adaptive weedy traits, including semi-dwarfism, delayed heading, high shattering, and superior seed storability, facilitating its persistence in field conditions. These findings provide critical insights for integrated weed management and cultivar purity strategies, emphasizing the importance of certified seed use, stringent field hygiene, and disruption of weedy rice reproductive cycles.